Semiotics Approach on Verbal Signs in Would You Care More IF I Was A Panda? - Wishnawa, Anak Agung Gede Hari; Sudipa, I Nengah; Sukarini, Ni Wayan (Humanis; Vol 25 No 1 (2021), 2021)
This study is aimed at identifying the verbal signs with their mode and connotative meaning of an advertisement. The data of this study was a wildlife advertisement entitled Would You Care More IF I Was A Panda? (2011) created by Ogilvy and published by World Wild Life. The data were collected using documentation method with note-taking technique. The data were analyzed qualitatively using Peirce’s semiotic theory to identify the verbal signs with their mode and Leech meaning theory to analyze the connotative meaning of the sign. The result of this study shown that there were three verbal signs found in the advertisements that belong to symbolic signs in the form of the combination of alphabets. The verbal signs consist of representamen, interpretant, and object. The connotative meanings are expressed in words, phrases, or sentences with the interpretation based on knowledge, emotion, and imagination.